Evidence and recommendations on the use of telemedicine for the management of arterial hypertension: An international expert position paper - Omboni, S; McManus, RJ; Bosworth, HB; Chappell, LC; Green, BB; Kario, K; Logan, AG; Magid, DJ; Mckinstry, B; Margolis, KL; Parati, G; Wakefield, BJ (American Heart Association, 2020)
Telemedicine allows the remote exchange of medical data between patients and healthcare professionals. It is used to increase patients’ access to care and provide effective healthcare services at a distance. During the recent coronavirus disease 2019 (COVID-19) pandemic, telemedicine has thrived and emerged worldwide as an indispensable resource to improve the management of isolated patients due to lockdown or shielding, including those with hypertension. The best proposed healthcare model for telemedicine in hypertension management should include remote monitoring and transmission of vital signs (notably blood pressure) and medication adherence plus education on lifestyle and risk factors, with video consultation as an option. The use of mixed automated feedback services with supervision of a multidisciplinary clinical team (physician, nurse, or pharmacist) is the ideal approach. The indications include screening for suspected hypertension, management of older adults, medically underserved people, high-risk hypertensive patients, patients with multiple diseases, and those isolated due to pandemics or national emergencies.